Board governance, diversity and efficiency: evidence from ASEAN-5 commercial banks - Ramly, Zulkufly; Chan, Sok Gee; Sapiei, Noor Sharoja; Mustapha, Mohd Zulkhairi (UUM College of Law, Government and International Studies Universiti Utara Malaysia, 2014)
The role of sound corporate governance in the banking industry is exacerbated following the disastrous effects of the Asian Financial Crisis and the Global Financial Crisis in in 1998 and 2008 respectively. A common theme to the crises was the tendency of banks to engage in risky business such as off-balance sheet and imprudent lending activities, which contributed to the failure in resource allocation and of the payment system. A key aspect of corporate governance is the effectiveness of the board of directors to steer commercial banks to greater accountability and ultimately enhancing performance. This study examines the effect of board governance and diversity on the efficiency of commercial banks in Malaysia, Indonesia, Thailand, Singapore and the Philippines or ASEAN-5. Using unbalanced panel data from 1998 to 2012, the results of Generalized Least Squares regression show that board size, ratio of independent directors and board diversity variables have positive effect on bank efficiency. However, the net effect of one board governance mechanism is more likely to be contingent on the level of corporate outcome that it is expected to influence. High efficiency banks seem to benefit from a larger board size, higher ratio of independent directors and board diversity. This study provides supporting evidence for the results of prior studies that showed that the effects of board size and board independence vary and is more likely to be contingent on the level of corporate outcome that it is expected to influence.